Analisis Sumber dan Penggunaan Modal Kerja Serta Profitabilitas Perusahaan Pada PT. PP London Sumatera Indonesia Tbk - Indah Mayang Sari; Yenni Samri Juliati Nasution; Laylan Syafina (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Planning, monitoring and management of working capital in the future is based on reporting the sources and uses of working capital. This study aims to determine the source and use of working capital PT. PP London Sumatra Indonesia Tbk and to determine the level of company profitability. This research method used is descriptive qualitative method. Sources of data used are secondary data using the company's financial statements in the form of balance sheets and profit and loss. The results showed that the largest source of working capital came from undetermined retained earnings and employee benefits liabilities, while the largest use of working capital was used for investment in associates and the purchase of mature plantations. To calculate the company's profitability using the ratio of Gross Profit Margin, Net Profit Margin, Return on Assets and Return on Equity. Based on the analysis that has been done, it is known that the increase in working capital occurs because the source of working capital is greater than its use. On the other hand, a decrease in working capital occurs due to the use of working capital is higher than the source.